การประกอบสร้างภาพเพื่อการโหยหาอดีตในรายการ "วันวานยังหวานอยู่" - สุวรรณมาศ เหล็กงาม (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The objectives of this qualitative research were to study 1) exploring contents that reflect past images in "Wan Warn Yang Wan Yoo" Program; 2) analyzing a method of social construction of nostalgia in "Wan Warn Yang Wan Yoo" Program; and 3) analyzing and comparing the interest in watching the program and understanding the meaning of past images presented by "Wan Warn Yang Wan Yoo" Program of old generation and new generation of viewers. The study was based on 1) the textual analysis approach; 2) in-dept interviews with program production team; 3) in-dept interview with audiences. It was found from the research that contents of "Wan Warn Yang Wan Yoo" Program reflects past images in many aspects that would reflect the past images, both negative and positive. According to the analysis of contents, it was found that 1) the contents of program contain past of every generations; 2) the contents of program contain past images of celebrities more than past images of society; 3) the program contains contents reflecting past images in 2 ways that are contents reflecting passed images in the past and contents reflecting the beautiful ones in the past but is lost in the current society. The characteristics of presentation of past contents would be for social construction meaning in 2 types that are retro and nostalgia.Method of a social construction of nostalgia in "Wan Warn Yang Wan Yoo" Program shows the characteristics that is consistent with postmodernism concept in 5 items that are hybrid, simulation, non-linear, cut and paste, and repetition. It was found on the issue of audience that old generation and new generation pay attention on watching the program conducted by hosts and the attention in the presentation of past contents. On interpretation, it was found that 1) factor of differences on stock of knowledge from experience of each viewer would affect decoding more than factor on difference of ages ; 2) the interpretation of viewers mostly are retro way and only some of a few interpret it as Nostalgia; 3) important factors that affect interpretation is experience of each viewer to be linked with the past images presented by "Wan Warn Yang Wan Yoo" Program.